(untitled) (CIPEEX, 2024)
This research explores the vacation regime in the Brazilian legal context, an inalienable social right that, after 12 months of an employment contract, provides the worker with a period for physical and psychological recovery. The objective of the research is to analyze the constitutional bases and practical implications of the right to disconnect, highlighting the importance of annual rest not only for workers’ health, but also for their productivity and psychological well-being. The theme reflects the importance of analyzing the contemporary challenges faced by workers during the global COVID-19 pandemic, especially in contexts of high labor demand and occupational stress. By outlining the historical evolution of vacation laws and exploring the economic, social and cultural motivations that support the granting of vacations, this analysis aims to provide a comprehensive and contextualized understanding of the impact of vacations on the relationship between employee and employer in Brazil. A bibliographical review was used to understand the topic and its impact on society, with the aim of collaborating with the improvement of employee rights. Thus, after analyzing publications in books, scientific articles and other academic productions, the research found proposals for changes in legislation, to contemplate workers’ right to disconnect. It was possible to conclude that the topic is not yet positive in the Brazilian legal system, but there is a movement towards its inclusion in legislation.